2005
DOI: 10.1016/j.carres.2005.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the methyl ester of hyaluronan and its enzymatic degradation

Abstract: A methyl ester of hyaluronan in which the carboxyl groups were fully esterified was prepared using trimethylsilyl diazomethane. This derivative, while not depolymerized by hyaluronan lyases or hyaluronan hydrolases, was a substrate for both chondroitin ACI lyase (EC 4.2.2.5) from Flavobacterium heparinum and chondroitin ACII lyase (EC 4.2.2.5) from Arthrobacter aurescens. The major product isolated in these depolymerization reactions was methyl α-L-threo-hex-4-enepyranosyluronate-(1→3)-2-acetamido-2-deoxy-α,β-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…c in the spectrum of fraction dp 6 are H-1 of methyl 2-acetamido-2-deoxy-D-galactofuranoside, ÀCOOCH 3 of glucuronate at the reducing end, and -OCH 3 of methyl 2-acetamido-2-deoxy-D-galactofuranoside. 1 H NMR analysis of oligosaccharides (dp [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] showed that each fraction was remarkably pure having a single major component (Fig. 3).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…c in the spectrum of fraction dp 6 are H-1 of methyl 2-acetamido-2-deoxy-D-galactofuranoside, ÀCOOCH 3 of glucuronate at the reducing end, and -OCH 3 of methyl 2-acetamido-2-deoxy-D-galactofuranoside. 1 H NMR analysis of oligosaccharides (dp [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] showed that each fraction was remarkably pure having a single major component (Fig. 3).…”
Section: Resultsmentioning
confidence: 98%
“…The mildest approach, and that typically preferred by our laboratory, is controlled enzymatic depolymerization. 7 Endolytic chondroitin/ dermatan lyases ACI, B and ABC, as well as testicular hyaluronan hydrolase, have been used to prepare pure oligosaccharides ranging in size from disaccharide (degree of polymerization (dp) 2) to dodecasaccharide (dp 12). 8,9 This method requires substantial purification because structural (sequence) variability gives rise to multiple oligosaccharides of each size.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HA esters can be synthetized using diazomethane as activator of the carboxyl groups [168]. All these reactions proceed in DMSO from the TBA salt of HA.…”
Section: Modification Of Ha Carboxyl Groupsmentioning
confidence: 99%
“…The low K M observed for C-OMe (comparable to CS-A) might be ascribed to the contribution of hydrophobic interactions between the methyl ester and the enzyme, replacing ionic interactions lost through the desulfonation and methyl esterification of the substrate. Both chondroitinase AC I from F. heparinum and chondroitinase AC II from A. aurescens were demonstrated by the Toida laboratory to be capable of depolymerizing hyaluronan O-methyl ester (Hirano et al, 2005).…”
Section: Chondroitin Lyase Structures and Mechanismmentioning
confidence: 99%